促進國小教師摘要策略教學的專業發展 Professional Development of Elementary School Teachers to Promote their Teaching of Summarization Strategy - 陸怡琮 I-Chung Lu (National Changhua University of Education, 2017)
本研究的目的在發展一個促進教師摘要策略教學專業的模式，並以兩位國小教師參與摘要策略教學研究為例，探討在此模式下教師在閱讀策略教學專業上的改變。閱讀策略教師專業發展模式包含了教學實踐、實務社群、與教學省思三個成分；亦即透過設計並實施教學、在實務社群中與專家及同儕合作與對話，以及對教學不斷回顧與省思等作法，促成教師在策略教學知能上的成長。研究歷程中蒐集會議記錄、教師省思、與教師設計的教案與學習單進行內容分析。結果顯示，兩位教師對摘要策略執行程序、摘要策略教學程序、摘要策略學習相關因素、與不同能力學生的摘要表現與教學因應等這些教學知識都有清楚理解，也對學生學習成效與自己在閱讀策略教學知識上的成長有所體認。 The purpose of this study is to develop a model for teacher professional development in teaching summarization strategy, and to explore two elementary school teachers' professional development in reading strategy instruction through their participation in this study. The teacher professional development model consists of three components: teaching practices, community of practices, and teacher reflection. That is, the professional growth of teachers' knowledge and skills in reading strategy instruction was realized as they were involved in designing lesson plans and implementing instructional activities in classrooms, participating in a professional community where they collaborated and interacted with a reading expert and a teacher colleague, and continuously reflecting on their teaching practices. Meeting minutes, teacher reflections, and teacher-created lesson plans and learning sheets were collected and analyzed. The results indicated that the teachers developed an increasing understanding of the procedure of summarizing, the instructional procedure of summarizing, the factors influencing students' learning of summarization, how students of diverse abilities summarized differently, and how instruction could adapt to students' individual differences. The teachers also observed their students' progress in summary writing, and reported their own growth in regard to the pedagogical knowledge of reading strategy instruction.